ECO-LITERACY: WHICH BETTER EITHER JOINING STUDY GROUP OR SELF STUDY? - Ade Suryanda (JURNAL PENA SAINS, 2019)
Eco-literacy is one aspect that is important for students to resolve the current environmental issue and sustainable living. Eco--literacy has three dimensions of caring, practical competence, and knowledge. One of the things that can build an Eco-literacy is participation in study groups. This study aims to describe the differences in the eco-literacy of biology students based on participation in study groups. This research was conducted at Universitas Negeri Jakarta on May 2018. The research method used was Ex Post Facto. There were two different sample groups; the first group was X1 contain by students who participated in the study group, and the other group X2 contain by students who had not participated in the study group. The number of the sample from each group was 32 biology students’ year 2015. The data score of Eco literacy was taken using an eco-literacy questionnaire. Data were analyzed with t-test at significance level α = 0,05. From the results of the analysis, there were no significant differences between the eco-literacy of students participating in the study group and students who did not participate in the study group.